HLA types in patients with rheumatoid arthritis developing leucopenia after both gold and sulphasalazine treatment. Issue 7 (July 1989) - Bliddal, H; Eiberg, B; Helin, P; Svejgaard, A
Abstract : HLA types, especially HLA-DR3, are associated with the development of toxic reactions in patients with rheumatoid arthritis after treatment with gold or D-penicillamine. In this study, after treatment with sulphasalazine, leucopenia was observed in three patients, who all had a history of leucopenia after previous gold treatment. The HLA types of these patients did not include HLA-DR3; the two patients developing mild leucopenia had HLA-DR2 and the one developing agranulocytosis had HLA-DR4.